Factors Affecting Gold Pawn Customer Satisfaction in Palangkaraya Central Kalimantan - Yurni, Yurni; Misra, Isra; Jelita, Jelita; Sadikin, Ali (Al-Iqtishadiyah: Ekonomi Syariah dan Hukum Ekonomi Syariah, 2024)
The purpose of this research is to find out the factors that influence customer satisfaction such as the amount of fees and late fees for gold pawning customers at Pawnshops in the city of Palangka Raya. This research is ex post facto in which this study looks at the direct influence between the independent variable and the dependent variable. This study uses a quantitative approach with multiple linear regression. The research population was all 705 gold pawning customers with a sample of 225 customers, the sample was determined using the Slovin technique with a tolerance of 5%. Data analysis used multiple linear regression with t, F and R Square tests. The results showed that the amount of ujrah and late fines had a significant positive effect on the satisfaction of Pawn Pawn customers in Palangka Raya. This is evidenced that the calculated t value is much greater than t table (variables X 1 11.590> 1.969 and X 2 7.783> 1.969) and the calculated F value is greater than F table (98.255> 3.031). Then the contribution value of R Square is 0.438, where it can be seen that the contribution of the independent variable to the dependent variable is 43.8%.